2022
DOI: 10.3390/healthcare10020392
|View full text |Cite
|
Sign up to set email alerts
|

Is It Useful to Question the Recovery Behaviour of Patients with ME/CFS or Long COVID?

Abstract: For the last few decades, medical guidelines have recommended treating patients with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) with graded exercise therapy (GET) and cognitive behavioural therapy (CBT). Moreover, doctors have questioned the recovery behaviour of these patients and stimulated them to follow these treatments so that they would be able to go back to work. In this article, we reviewed trials of GET and CBT for ME/CFS that reported on work status before and after treatment to answ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 56 publications
0
12
1
2
Order By: Relevance
“…This is also consistent with recommendations for rehabilitation for outpatients with post-COVID/long-COVID symptoms [ 32 ]. However, these findings are contrary to other studies that found that graded physical exercise can be detrimental in treating fatigue [ 33 ]. Thus, further research on this matter is urgently needed.…”
Section: Discussioncontrasting
confidence: 99%
“…This is also consistent with recommendations for rehabilitation for outpatients with post-COVID/long-COVID symptoms [ 32 ]. However, these findings are contrary to other studies that found that graded physical exercise can be detrimental in treating fatigue [ 33 ]. Thus, further research on this matter is urgently needed.…”
Section: Discussioncontrasting
confidence: 99%
“…To ensure people with long COVID and associated conditions can receive adequate care now, professional societies and government agencies must educate the health-care and research workforce on these illnesses, including the history of and current best practices for ME/CFS to not repeat mistakes of the past, which have worsened patients’ prognoses. The research community has made a misstep in its efforts to treat ME/CFS 199 , and some physicians, poorly educated in the aetiology and pathophysiology of the disorder, still advise patients to pursue harmful interventions such as graded exercise therapy and cognitive behavioural therapy, despite the injury that these interventions cause 200 and the fact that they are explicitly not advised as treatments 163 , 164 , 166 .…”
Section: Challenges and Recommendationsmentioning
confidence: 99%
“…Future interdisciplinary research needs to establish whether there are biological, behavioral, and psychological predictors that determine the effect of vaccination after infection on functional immune response and recovery processes [ 23 , 25 ]. Although both cognitive behavioral therapy and graded exercise therapy appear rather ineffective and have potential side effects, some lifestyle changes, such as plant-based diets, have been found to be promising in supporting post-/long-COVID management [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important because limited workability is problematic not only for the individual (because of limited social participation and economic demands) but also for society (because of limited productivity and skills shortage, and costly reintegration demands to be covered by the social welfare system). This needs to be addressed based on theories and evidence, including psychological and behavioral approaches (e.g., [ 49 ]), immune phenotypes [ 54 ], and adaptive-like NK cell phenotype [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%